Plan de negocios para la creación de un bar – restaurante temático de las series de comedia más famosas de todos los tiempos - Torres Caviedes, Ana Belén (2016)
The present job proposes a business plan to create a thematic bar – restaurant in Quito, based on the most famous comedy series. The aim of this study is to determine the feasibility of the implementation of this project, both commercially and financially. The business idea arises from the need of millennials for a place where they can feel identified and where they can spend time with their family, friends or couple. Currently the industry is soaked, there is a lot of places that do the same as it is going to be done, however it still maintains growth so the aim is that the company uses its differentiation to manage a stable positioning within the industry accommodation and food services. The target market consists of people between 20 and 45 years old, who enjoy hanging out with their be loved ones, middle socioeconomic level to medium high, that work and / or study. The objective of this project is to create a unique and exclusive environment where the target market feels comfortable, come back and recommend to more people. Whereas it is a new project which is situated in very strong market; competition strategies need to be run very well in the defined market with the aim of penetrating the market and stay there. The capital required for this project is $ 76.652,00, which covers the initial investment (working capital, assets, and intangibles) the same that will be financed 50% by its shareholders and 50% by a three-year loan. Through the financial evaluation it is determined that the proposal is financially viable because it generates profitability and is attractive to investment.